THE EFFECT OF AURASMA AUGMENTED REALITY (AR) TO ENHANCE YOUNG LEARNERS’ VOCABULARY MASTERY - Hudaya, Anwar; Sadikin, Irma Savitri (PROJECT (Professional Journal of English Education), 2019)
The aim of this study is to analyze the difference of young learners’ vocabulary mastery through Aurasma Augmented Reality (AR). The research was conducted in SDN 1 Jayagiri Lembang and the sample of this study was gained from two classes of sixth grade. One class was treated using AR, while another class was treated without AR in teaching vocabulary. The data were gathered from pre-test and post-test. The result of this study revealed that young learners could improve their vocabulary mastery through augmented reality (AR). It can be inferred that there is a significant difference from students’ pre-test and post-test result. Furthermore, the data from observation displayed a positive attitude during the students’ learning through Aurasma AR. Most of students participated actively in the classroom, they showed high curiosity, and they enjoyed and felt enthusiastic in learning vocabulary.